Ações universitárias de educação empreendedora para crianças e adolescentes - Cabral, Kamylle Sumaya Verçosa (Brasil, 2024)
Entrepreneurial education can be understood as a constantly evolving process, characterized by awareness, association and application of knowledge. Emphasizing the promotion of critical thinking and the ability of students to analyze and interpret, aiming to develop entrepreneurial skills and abilities, characteristics that are intrinsic to individuals. The objective of this study was to investigate how the Administration course at the Institute of Social Sciences, Education and Animal Science has worked on entrepreneurship with children and adolescents. The sample was made up of 8 professors from the Administration course. The semi-structured interview was used as an instrument for data collection with questions regarding the carrying out of Teaching, Research and Extension Activities aimed at children and adolescents. As a result, the teachers reported that they did not carry out any teaching and research activities on the subject of entrepreneurship with children, however, in terms of extension, 4 teachers highlighted having carried out actions on the topic of entrepreneurship for children and adolescents. The findings of the present study show that it is necessary to develop actions so that children and adolescents can take part in activities to understand the concept of autonomy, providing the freedom so that they can choose both the path of entrepreneurship and have an entrepreneurial profile, even that are not actively linked to direct entrepreneurship and develop it throughout their lives. For future studies on the topic, it is suggested to analyze the impacts of entrepreneurial education on the development of entrepreneurial skills, attitudes and behaviors in students of different ages in the educational context.